2018
DOI: 10.3354/dao03276
|View full text |Cite
|
Sign up to set email alerts
|

Parvicapsula curvatura n. sp. in cultured olive flounder Paralichthys olivaceus and phylogenetic characteristics of the genus Parvicapsula

Abstract: Parvicapsula curvatura n. sp. (Myxozoa; Bivalvulida) was found in the urinary bladder of olive flounder Paralichthys olivaceus cultured in a fish farm on Jeju Island, ROK. When laterally viewed, the parasite has asymmetrical curved spores that measure 9.6-11.6 µm in length. Furthermore, it has 2 subspherical polar capsules at the apex. Based on the phenotypical traits, it is most similar to P. limandae but differs in the shape of polar capsule, locality, and host specificity (family level). BLAST analysis indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Other previous studies revealed that phylogeny of myxosporeans have a specific relation with biological traits such as host specificity, infection site tropism, and morphology [28,37,38]. Interestingly, the Sinuolinea spp.…”
Section: Dicussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Other previous studies revealed that phylogeny of myxosporeans have a specific relation with biological traits such as host specificity, infection site tropism, and morphology [28,37,38]. Interestingly, the Sinuolinea spp.…”
Section: Dicussionmentioning
confidence: 97%
“…In our previous study, we revealed the 18S rDNA sequence of P. curvatura which misidentified as S. capsularis sequence [28]. Because the P. curvatura was not observed in material with light microscopy and we used universal primers (such as 18e, ERIB1 and ERIB10), which have been used to PCR for other myxosporeans [29,30], we confused the sequence.…”
Section: Dicussionmentioning
confidence: 99%
“…Olive flounder, Paralichthys olivaceus, is an important fish species cultured in Korea, and there have been several reports of myxosporean infections (Enteromyxum leei, Parvicapsula anisocaudata, P. curvatura, and Sinuolinea capsularis), including Kudoa spp. (K. septempunctata and K. paralichthys), in the fish [15][16][17][18][19]. The Fish Vaccine Research Center has been monitoring the parasitic infections of olive flounder cultured in Jeju island and has isolated another Kudoa sp.…”
mentioning
confidence: 99%
“…DNA was extracted from partially purified parasites using the AccuPrep Genomic DNA Extraction Kit (Bioneer, Daejeon, Korea) following the manufacturer's instructions. Portions of 18S and 28S rDNA were amplified by PCR using a combination of primers that we (28S-KO2000F: 5′ -CTGTCCGTACCGAATCCG-3′) and other groups (18S-18e: 5′ -CTGGTTGATCCTGCCAGT-3′, 18S-MyxospecF: 5′-TTCT-GCCCTATCAACTWGTTG-3′, 18S-MyxospecR: 5′-GGTTTCN CDGRGGGMCCAAC-3′, 18S-ERIB10: 5′-CTTCCGCAG-GTTCACCTA-3′, 28S-Kt28SF: 5′-CAAGACTACCTGCTGAAC-3′, 28S-NLF1050: 5′-AATCGAACCATCTAGTAGCTGG-3′, 28S-NLR1270: 5′-TTCATCCCGCATCGCCAGTTC-3′, 28S-NLR1694(mo): 5′-GTTAGGCAATGGCTTAGGACC-3′, 28S-3R: 5′-GAGCACTGGGCAGAAATC-3′, 28S-NLR3113(mo): 5′-GTC-TAAACCCAGCTCACGTTC-3′, and 28S-NLR3284: 5′-TTCT-GACTTAGAGGCGTTCAG-3′) have designed [2,16,[21][22][23][24][25]. PCR products were treated with the AccuPrep Genomic PCR Purification Kit (Bioneer) to remove excess primers and dNTPs, and were directly sequenced using BigDyeTM Terminator v3.1 in an ABI 3730xl Sequencer.…”
mentioning
confidence: 99%